The Review of Islamic Law in Showing off the Bride and Groom in Front of an Invitation : Perspective of KH. Abdul Hamid bin Itsbat Banyuanyar in the Book of Tarjuman - Samheri, Samheri; Ludfi, Ludfi (Sekolah Tinggi Agama Islam (STAI) Darul Ulum Banyuanyar Pamekasan, 2023)
Abstract Indonesian society generally displays the bride and groom in front of guests and the general public. In fact, this has spread in various areas to remote villages. Each region has its own characteristics in celebrating the momentum of this celebration/wedding party. However, almost evenly in all regions, when the guests poured out, the bride and groom were displayed in front of the guests and even the general public. The bride and groom were beautifully made up, sitting on a throne with stunning decorations and reasonable costs. So, what is the law on displaying the bride and groom in front of invitations? What is the view of the Madurese cleric KH Abdul Hamid bin Itsbat Banyuanyar Pamekasan regarding the display of the bride and groom in front of the guests and the general public as written in the Tarjuman Book which is famous among families, students, alumni and sympathizers of the Banyuanyar Islamic Boarding School. The research method used in this research is qualitative research, which is a type of library research. This research was carried out so that the wedding celebration which was recommended by the Prophet Muhammad could be carried out without losing its essence and not going beyond the boundaries of Sharia law. The findings of this research state that displaying the bride's bride in front of invitees and the general public is considered a disobedience that can lead her to the torment of hell in the end, that is what KH stated. Abdul Hamid bin Itsbat Banyuanyar Islamic Boarding School, in his book Tarjum